DESIGNING MODERN MALAY TRADITIONAL FOOD PRODUCTS WITH AN EMPHASIS ON LOCAL CULTURAL VALUES TO ENHANCE CULINARY TOURISM IMAGE - Siska Hasibuan; Eka Wulandari Surbakti; Khairunnisa Almadany (SEAN Institute, 2023)
Malay specialties have become part of Indonesia's priceless cultural heritage. The unique taste and distinctive image of these foods have attracted local and foreign tourists to explore Indonesia's culinary diversity. However, to maintain its existence and increase its attractiveness to tourists, typical Malay food products need to be continuously developed with a modern touch and emphasis on local cultural values. Therefore, this research will design the development of modern Malay specialty food products with an emphasis on local cultural values as an alternative to enrich the regional culinary repertoire and improve the image of culinary tourism. This research has an important urgency, namely to increase the attractiveness of culinary tourism, preserve local culture, increase the potential of culinary tourism, and contribute to the academic field. The methodology used in this research is descriptive qualitative and quantitative methods. This research will be conducted by conducting a survey of tourists and local communities about market preferences and needs for modern Malay specialty food products. In addition, this research will also involve local culinary and cultural experts to provide input in the design of modern Malay specialty food products with an emphasis on local cultural values. Trials of modern Malay specialty food products will be carried out to evaluate the quality and suitability of products with local preferences.